All-Arthroscopic Suprapectoral Versus Open Subpectoral Tenodesis of the Long Head of the Biceps Brachii. (May 2015) - Gombera, Mufaddal Mustafa; Kahlenberg, Cynthia A.; Nair, Rueben; Saltzman, Matthew D.; Terry, Michael A.
Background: Pathologic changes of the long head of the biceps tendon are a recognized source of shoulder pain in adults that can be treated with tenotomy or tenodesis when nonoperative measures are not effective. It is not clear whether arthroscopic or open biceps tenodesis has a clinical advantage. Hypothesis: Pain relief and shoulder function after all-arthroscopic suprapectoral biceps tenodesis are similar to outcomes after an open subpectoral tenodesis. Study Design: Cohort study; Level of evidence, 3. Methods: A prospective database was reviewed for patients undergoing an all-arthroscopic suprapectoral or open subpectoral biceps tenodesis. Adult patients with a minimum 18-month follow-up were included. Patients undergoing a concomitant rotator cuff or labral repair were excluded. The groups were matched to age within 3 years, sex, and time to follow-up within 3 months. Pain improvement, development of a "Popeye" deformity, muscle cramping, postoperative American Shoulder and Elbow Surgeons scores, satisfaction scores, and complications were evaluated. Results: Forty-six patients (23 all-arthroscopic, 23 open) with an average age of 57.2 years (range, 45-70 years) were evaluated at a mean follow-up of 30.1 months (range, 21.1-44.9 months). No patients in either group developed a Popeye deformity or complained of arm cramping. There was no significant difference in mean American Shoulder and Elbow Surgeons scores between the open and all-arthroscopic groups (92.3 vs 88.9; P = .42); similarly, there was no significant difference in patient satisfaction scores between the groups (8.9 vs 9.1; P = .73). Eighteen patients (78.3%) in the arthroscopic cohort and 16 (69.6%) in the open cohort fully returned to athletic activity ( P = .50). Eight patients (34.8%) in the arthroscopic group and 10 (39.1%) in the open group reported pain at night or with heavy activities. There were no complications in the all-arthroscopic group. There were 2 complications in the open group that resolved by final follow-up. Conclusion: Biceps tenodesis remains a reliable treatment for pathologic abnormality of the long head of the biceps. Patients undergoing an all-arthroscopic suprapectoral tenodesis in the distal aspect or distal to the bicipital groove showed similar pain relief and clinical outcomes as compared with patients undergoing open subpectoral tenodesis. Open subpectoral biceps tenodesis may carry a higher complication risk secondary to a more invasive technique.